The Designation Degree of Tool Wear after Machining of the Surface Layer of Duplex Stainless Steel - Tomasz Dyl (MDPI AG, 2021)
This paper presents problems related to the machining of the surface layer. It is important that steel structures are used in material engineering and machine construction. Austenitic, ferritic, martensitic and two-phase corrosion resistant steel was widely used in the petrochemical and shipbuilding industries. Duplex stainless steel was used in sea water and acid installations. The shafts of centrifugal pumps can be made of stainless steel and are used in acid or seawater pumps. The surface layer of corrosion resistant steel shafts must have a low surface roughness. Machine elements made of stainless steel, and in particular of the duplex type, are difficult-to-cut materials. This article aims to study the effect of parameters on tool life and tool wear. The influence of technological parameters such as depth of cut, cutting speed, feed on maximum value tool wear is presented. The treatment of the surface layer was performed using carbide inserts. The highest wear and the lowest roughness were used as selection criteria. This problem is a significant issue due to the ability of the machine parts for the required reliable operation of devices and machines. To determine the degree of tool wear to increase of the surface layer quality after shaping DSS.